2007
DOI: 10.1177/095632020701800205
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Inhibition of HIV Type 1 Reverse Transcriptase-Bearing NRTI-associated Mutations by Apricitabine Triphosphate

Abstract: We wished to investigate the effects of various mutations in HIV-1 reverse transcriptase (RT) on biochemical inhibition by the active form of a novel nucleoside termed apricitabine. Accordingly, we studied the efficiency of chain-termination mediated by apricitabine triphosphate (TP) in cellfree assays that used either recombinant wild-type or mutated RTs. We also performed steady-statekinetics and primer-unblocking assays. Subtype C RTs were also analysed. The results showed that the K65R mutation in RT cause… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Because a proportion of nt polymorphisms that distinguish the two subtypes do not result in changes of the amino acid sequence, it is not surprising that RTs derived from either subtype B or C are similar enzymatically [46], [47], [48], [50].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because a proportion of nt polymorphisms that distinguish the two subtypes do not result in changes of the amino acid sequence, it is not surprising that RTs derived from either subtype B or C are similar enzymatically [46], [47], [48], [50].…”
Section: Resultsmentioning
confidence: 99%
“…K65R-associated treatment failures are uncommon and usually develop at rates between 0 and 3% [42], [43], [44], [45]. To explore this discrepancy, biochemical analysis of the RT enzymes derived from both subtypes were performed and showed that they are very similar; the subtype origin of RT cannot explain the discrepancies observed with respect to K65R development [46], [47].…”
Section: Introductionmentioning
confidence: 99%
“…These experimental observations favor the development of NRTIs that resist excision, such as apricitabine, that are currently in clinical trials [8385]. Moreover, we predict that allosteric drug inhibitors, with similar mechanism of action as NNRTIs and PIs, will be effective against HIV cell-to-cell transmission on their own.…”
Section: Therapeutically Blocking Cell-to-cell Transmission Of Hivmentioning
confidence: 95%
“…The Km for dATP and the K i for TFV-DP were determined by filter binding assays as described previously [ 36 ]. In brief, 200 nM dPR were heat-annealed to 300 nM subtype C HIV-1 PBS RNA in a buffer containing 50 mM Tris-HCl pH 7.8 and 50 mM NaCl.…”
Section: Methodsmentioning
confidence: 99%
“…Incorporated radioactivity was measured by liquid scintillation counting. Kinetic constants were determined using Graphpad Prism 4.0 software as described [ 36 ].…”
Section: Methodsmentioning
confidence: 99%